2000
DOI: 10.1093/brain/123.9.1767
|View full text |Cite
|
Sign up to set email alerts
|

The pedunculopontine nucleus and Parkinson's disease

Abstract: Akinesia and gait disturbances are particularly incapacitating for patients with Parkinson's disease. The anatomical and physiological substrates for these disturbances are poorly understood. The pedunculopontine nucleus (PPN) is thought to be involved in the initiation and modulation of gait and other stereotyped movements, because electrical stimulation and the application of neuroactive substances in the PPN can elicit locomotor activity in experimental animals. Glutamatergic neurones of the PPNd (pars diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
541
2
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 740 publications
(592 citation statements)
references
References 131 publications
23
541
2
12
Order By: Relevance
“…In the current study, we found that the effects of STN DBS on regional metabolism were generally similar to those identified following subthalamotomy (Su et al, 2001;Trošt et al, 2003). Specifically, declines in glucose utilization during STN stimulation were detected in the rostral pons and midbrain in proximity to the upper portion of the pedunculopontine nucleus (PPN, Pahapill and Lozano, 2000). Metabolic reductions in these regions have also been reported following STN lesioning (Su et al, 2001;Trošt et al, 2003), suggesting diminished outflow from the STN target nucleus to the brainstem in both interventions.…”
Section: Metabolic Changes With Stn Stimulationsupporting
confidence: 75%
“…In the current study, we found that the effects of STN DBS on regional metabolism were generally similar to those identified following subthalamotomy (Su et al, 2001;Trošt et al, 2003). Specifically, declines in glucose utilization during STN stimulation were detected in the rostral pons and midbrain in proximity to the upper portion of the pedunculopontine nucleus (PPN, Pahapill and Lozano, 2000). Metabolic reductions in these regions have also been reported following STN lesioning (Su et al, 2001;Trošt et al, 2003), suggesting diminished outflow from the STN target nucleus to the brainstem in both interventions.…”
Section: Metabolic Changes With Stn Stimulationsupporting
confidence: 75%
“…The PPN has extensive connections with the basal ganglia 5,11 , receiving strong inhibitory inputs from both the globus pallidus internus and substantia nigra 41 . Thus, the reduction in PPN activity may be mediated by inhibitory input from the basal ganglia 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the motor symptoms of PD are responsive to dopamine replacement, gait freezing and postural instability respond poorly. The pathophysiology of these gait disturbances is poorly understood, but their late onset and resistance to levodopa has led to the suggestion that they may result from pathology in nondopaminergic structures involved in locomotion 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholinergic cells predominate in PPNc, but PPNc and anteromedial pars dissipata also contain large populations of GABAergic or glutamatergic neurons [77][78][79]. The input and output relationships of the various neuron groups in the PPN have not been precisely determined, but it is known that the nucleus gives rise to projections to the basal ganglia, thalamus, basal forebrain, reticular formation, and spinal cord [69,74,[80][81][82][83][84][85][86][87][88][89][90][91][92][93], thus being, at the same time, part of the extended basal ganglia family of nuclei [74], and a conduit of descending basal ganglia outputs. The function(s) of this nucleus are poorly understood, although portions of the (primate) PPN are implicated in the control of gait and balance because of overlap with the physiologically identified mesencephalic locomotor region and possibly other motor functions (see below).…”
Section: Functional/anatomic Considerations Of the Basal Ganglia Circmentioning
confidence: 99%